Unmarried Boomers Confront Old Age: A National Portrait - Lin, I-Fen (Oxford University Press, 2012)
PURPOSE OF THE STUDY: Our study provides a national portrait of the Baby Boom generation, paying particular attention to the heterogeneity among unmarried Boomers and whether it operates similarly among women versus men. DESIGN AND METHODS: We used the 1980, 1990, and 2000 Census 5% samples and the 2009 American Community Survey (ACS) to document the trends in the share and marital status composition of the unmarried population during midlife. Using the 2009 ACS, we developed a sociodemographic portrait of Baby Boomers according to marital status. RESULTS: One in three Baby Boomers was unmarried. The vast majority of these unmarried Boomers were either divorced or never-married; just 10% were widowed. Unmarried Boomers faced greater economic, health, and social vulnerabilities compared to married Boomers. Divorced Boomers had more economic resources and better health than widowed and never-married Boomers. Widows appeared to be the most disadvantaged among Boomer women, whereas never-marrieds were the least advantaged among Boomer men. IMPLICATIONS: The rise in unmarrieds at midlife leaves Baby Boomers vulnerable to the vagaries of aging. Health care and social service providers as well as policy makers must recognize the various risk profiles of different unmarried Boomers to ensure that all Boomers age well and that society is able to provide adequate services to all Boomers, regardless of marital status.